Device for dismantliing and assembling hard-to-separate mechanical assemblies on mechanical plants - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper presents a new technical solution, a device for dismantling and assembling parts of mechanical plant components which are not easily separable. The device design allows wide possibilities of application in maintenance and repair of hydro power plants, thermal power plants, and diesel electric generators, in motor industry, shipbuilding industry and navy, aircraft industry, and turbines in process industry. The device for dismantling and assembling is universal and easy to use. Its small weight makes it easy to transport to locations with machine facilities.